AKUISISI DI PERSIMPANGAN: Analisis Kinerja Keuangan Sebelum dan Sesudah Pengambilalihan pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2025 - Yosep Eka Putra; Salwa Assyfa Yusri; Sari Uswatun Hasanah; Suci Rahmadani; Viola Agnesya; Selfi Gusti Meliza (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the comparative financial performance of companies listed on the Indonesia Stock Exchange (IDX) before and after acquisitions during the 2020–2025 period. The methodology employs a quantitative approach utilizing comparative analysis based on secondary data from the financial statements of 18 companies that have undergone acquisitions. Financial performance is evaluated using Return on Assets (ROA), Current Ratio (CR), Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Earnings per Share (EPS). Normality testing was conducted using the Kolmogorov-Smirnov and Shapiro-Wilk methods. Given that the data were not normally distributed, hypothesis testing was performed using the non-parametric Mann-Whitney U test. The results indicate no significant differences in any of the financial ratios before and after acquisition, with significance values of 0.457 for ROA, 0.950 for CR, 0.601 for TATO, 0.438 for DER, and 0.716 for EPS. These findings suggest that acquisitions have not yet yielded a significant impact on corporate financial performance in the short term. This study contributes empirical evidence regarding the effectiveness of acquisitions among IDX-listed companies and offers insights for investors and corporate management when evaluating acquisition decisions and post-acquisition integration strategies.